Independent psychoanalysis today - Williams, Paul (Psychotherapist); Keene, John (Psychoanalyst); Derman, Sira (Karnac, 2012)
Independent Psychoanalysis Today is a book that shows how contemporary Independent psychoanalysts think and work. There are three themes to the book: Independent thinking including the theory of technique; exploration of clinical concepts and demonstrations of ways of working by some of the most prominent Independent clinicians practicing today; finally, the evolution and enduring impact of Independent ideas and the influence of past Independents on present ways of working.